Caracterização química e identidade genética de Dalbergia ecastaphyllum para produção de extratos padronizados - Melo, Lucyana Santos de Mendonça (2016)
The Dalbergia ecastaphyllum was determined as a botanical origin of Brazilian red propolis by chemical and molecular studies. This fact raised the amount of research on this plant species. The National Institute of Industrial Property granted the designation of origin red propolis and Alagoas propolis extract whose composition has, among other chemical compounds, formononetin and daidzeína markers. However, several studies have identified the chemical markers of this product in samples of D. ecastaphyllum and propolis of Sergipe. The objective of this work was to define the fingerprint D. ecastaphyllum of low São Francisco by chemical and molecular markers, in addition to evaluating the biological activity to enable the development of standardized extracts with known concentrations of active ingredients. The chromatographic profiles of plants and propolis showed similarity. The HPLC results showed that the different parts of the plant have similar chemical profiles. The compound gallic acid were identified in all plant parts, but only on the bark been found formononetin and biochanin A chemical markers. The fingerprint ESI(-)-MS and analyzes by UHPLC-MS were more accurate, because the compounds formononetin, biochanin A and daidzein were identified in all samples. The results of the sequencing for evaluation of the genetic identity of populations of Dalbergia demonstrated that they are highly homogeneous, having exactly the same haplotype for the analyzed region. All extracts were able to inhibit the development of clinical strains of S. aureus and P. aeruginosa. The compounds gallic acid and formononetin were identified, quantified and used as parameters for standardization of Dalbergia extract. The results of this study demonstrate that not all compounds present in the extracts possess activity against the microorganisms used and probably the combined action between them decreases the biological potency of gallic acid compound. To achieve effective antimicrobial activity in these samples can standardize the extract with a minimum amount of 1% gallic acid and 4% formononetin. According to the results D. ecastaphyllum low San Francisco have the same genetic characteristics and chemical profiles including presenting the chemical markers considered for Alagoas propolis. It is necessary to conduct more comparative studies between propolis the northeastern region to the possibility of geographical designation of origin be extended to other states. It is inferred that, compared to chemical markers, any part of the plant can be used. However, we suggest the use of bast as the preferred part of the plant for the production of extracts due to the higher concentration of compounds found. While correlation studies indicate that the compounds analyzed have antimicrobial activity, you need to evaluate the activity of these compounds isolated to confirm this hypothesis. The genetic similarity of plants and the presence of several chemical markers, as well as ease of propagation of this plant in cultivation system enables the operation of a new way of obtaining bioactive compounds directly from the inner bark of D.ecastaphyllum extracts.